2021
DOI: 10.1021/acs.iecr.1c02106
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–Alumina Coprecipitated Catalysts for Green Diesel Production

Abstract: Cobalt–alumina catalysts with high Co loading (35–70 wt %) were synthesized by coprecipitation. The influence of activation (reduction) temperature and the Co loading on their efficiency for green diesel production via selective deoxygenation (SDO) of solvent-free sunflower oil (SO) and waste cooking oil (WCO) has been investigated. The change of reduction temperature and the cobalt content caused remarkable changes in the physicochemical properties and catalytic behavior of the catalysts. A catalyst containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…H 2 -TPD experiments were implemented to determine the ability of Cu-CoGa catalysts for dissociating hydrogen (Figure 6A). In all cases, H 2 -TPD curves can be deconvoluted into three regions, which are attributed to the desorption of chemisorbed H 2 on metallic Cu 0 sites (50−150 °C) 47 and CoGaO x species (150−350 °C) 48 and spillover hydrogen from Cu 0 and CoGaO x species to the support (>350 °C), 49 respectively, as evidenced by the H 2 -TPD results of CuGa-0.4 and CoGa-0.4 reference samples (Figure S16A). As summarized in Table 2, the quantitative H 2 -TPD results reveal that the amount of H 2 desorbed from Cu 0 sites reaches the maximum in the Cu-CoGa-0.4 sample, well consistent with the results of N 2 O titration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H 2 -TPD experiments were implemented to determine the ability of Cu-CoGa catalysts for dissociating hydrogen (Figure 6A). In all cases, H 2 -TPD curves can be deconvoluted into three regions, which are attributed to the desorption of chemisorbed H 2 on metallic Cu 0 sites (50−150 °C) 47 and CoGaO x species (150−350 °C) 48 and spillover hydrogen from Cu 0 and CoGaO x species to the support (>350 °C), 49 respectively, as evidenced by the H 2 -TPD results of CuGa-0.4 and CoGa-0.4 reference samples (Figure S16A). As summarized in Table 2, the quantitative H 2 -TPD results reveal that the amount of H 2 desorbed from Cu 0 sites reaches the maximum in the Cu-CoGa-0.4 sample, well consistent with the results of N 2 O titration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The atmospheric distillation method ASTM D-86 is used for petroleum products and middle distillates. This method detects the boiling range for lots of different hydrocarbon distillates such as gasoline with or without oxygenates, diesel, and other light and middle distillates 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…The catalysts commonly applied in hydrotreatment are transition metal, for example, Ni-and CO-based catalysts as good conversion can be achieved [24][25][26]. The study by Liu et al concluded that the Ni supported on a porous carbon matrix synthesized at 400 • C was able to obtain a high conversion up to 90% under reaction conditions at 320 • C, 3 MPa, and 4 h of reaction time in cyclohexane.…”
Section: Figurementioning
confidence: 99%